PENGARUH LAHAN,AKSES JALAN DAN ATMOSFER PASAR TERHADAP LOYALITAS KONSUMEN DIPASAR SORE DESA KETAPANG KUALA TELUK BETUNG SELATAN - Iqbal Rahman; Alfyando Dwi Putra (Universitas Mitra Indonesia, 2023)
The purpose of this study was to determine the effect of Land, Road Access and Market Atmosphere on Consumer Loyalty in the Evening Market of Ketapang Kuala Teluk Betung Selatan Village. The data used in this study were primary data. Furthermore, the data collection technique used in this study was a survey which Use Google Forms to collect data. In this study the researchers used the t-test and coefficient-test methods with the help of the smart plss program version 2. Based on the results of the research, the R² value lies at 0 R² 1, an R² value close to 1, which means the model is getting better. Meanwhile, the value of R² which is zero means that there is no relationship between the dependent variable and the explanatory variable. From the table, with the location of R² 1 with a value of 0 0.58 1, this means that the variance of consumer loyalty is able to explain the variance of 0 ,58 Keywords :Land,Road Access,Market atmosfer and Cosumer Loyalty